All Optical Half Adder/Subtractor using Dark-bright Soliton Conversion Control - Sappasit Thongmee; Preecha P. Yupapin (My University, 2011)
We propose a new design of all-optical circuit using microring and nanoring devices, in which the simultaneous operation of half adder/subtractor arithmetic can be formed by using dark-bright soliton conversion control within the system. The input logic "0 "and "1" are performed by using dark and bright soliton pulses, respectively. By using the dark-bright soliton conversion behavior with in the π/2 phase shift device, the arithmetic unit can perform simultaneously at the drop and though port, respectively. In application, the proposed scheme is simple and flexible for performing the logic switching system, which can be used for advanced logical system.
Keywords: Subtractor; Optical Network Technologies